Distribuição de recursos florais de plantas melitófilas em uma área em restauração florestal em Holambra, São Paulo, Brasil - Santos, Elisangela Fernandes dos (2020)
Pollination is one of the most important ecosystem services for maintaining biodiversity, as it is a key process for restoring the function of altered ecosystems. It is largely carried out by bees both in agricultural and natural systems. Nevertheless, this process has been highly impacted by anthropogenic impacts in the environment. The restoration of these environments aims to reestablish these interactions by replacing the local flora. This work aimed to evaluate if the floristic composition of a restoration area is a place with important food resources for the bees. from the distribution of floral resources over a year. The floristic survey was made in a fragment under restoration inserted in an agricultural matrix, located in Holambra / SP. Field activities took place monthly from January to December 2018 in three parcels of 1,500m² each. Samples of flowering plant species were collected from each plot and the exsiccates were prepared and processed and incorporated into the UNESP campus Rio Claro Herbarium collection. Each species was identified and confirmed by experts, and information on the main pollination syndrome, habit, main floral resource offered to pollinators (pollen, nectar, oil) and origin (native or non-native) were obtained from specialized literature. To evaluate the distribution of floral resources during the year, we used circular analysis and applied the Rayleigh test (p) to identify the occurrence of seasonality and Pearson's index using the BioStat Pro 6.0 program to evaluate the occurrence or not of correlation between flowering and climatic factors such as temperature and temperature. precipitation. The families Asteraceae and Fabaceae presented the largest number of flowering species, with the most abundant species of herbaceous habit. About 75% of the identified plants were pollinated by bees, the most frequent syndrome. Among the melitophilous plants, the native species were the most frequent (70.5%) and in relation to the distribution of floral resources, the melitophilic plants presented seasonality in the flowering period, with peak in the rainy months, being the nectariferous species the most abundant. There were no representatives of non-native oil producing species. Regarding resource distribution in the stratification, native tree and shrub species flourished in greater numbers in the rainy season, while non-native species of these habits had a peak of flowering in the dry period. Native and non-native herbaceous plants bloomed most in the rainy months and lianas showed no flowering seasonality for nectar and pollen for both native and non-native species. The results showed that the vertical forest stratification is important for the supply of floral resources to pollinators, however herbaceous plants stood out in relation to the richness and abundance of flowering plants, both native and non-native, providing nectar, pollen and oil for the bees. These species are usually considered as weeds in agricultural environments being eliminated as a part of the management in these areas, extinguishing food sources for bees. The distribution of floral resources in stratification was quite variable, as floral resources were available in both dry and rainy periods of the year, highlighting the importance of the study area as an interesting place for bee survival. Verifying the distribution of floral resources is important because it provides information for the conservation of bees, showing the periods of abundance and food shortage, allowing the improvement of ecological management projects.